Inflammatory bowel disease: an immunity-mediated condition triggered by bacterial infection with Helicobacter hepaticus. - Cahill, R; Foltz, C; Fox, J; Dangler, C; Powrie, F; Schauer, D (1997)
Inflammatory bowel disease (IBD) is thought to result from either an abnormal immunological response to enteric flora or a normal immunological response to a specific pathogen. No study to date has combined both factors. The present studies were carried out with an immunologically manipulated mouse model of IBD. Mice homozygous for the severe combined immunodeficiency (scid) mutation develop IBD with adoptive transfer of CD4+ T cells expressing high levels of CD45RB (CD45RB(high) CD4+ T cells). These mice do not develop IBD in germfree conditions, implicating undefined intestinal flora in the pathogenesis of lesions. In controlled duplicate studies, the influence of a single murine pathogen, Helicobacter hepaticus, in combination with the abnormal immunological response on the development of IBD was assessed. The combination of H. hepaticus infection and CD45RB(high) CD4+ T-cell reconstitution resulted in severe disease expression similar to that observed in human IBD. This study demonstrates that IBD develops in mice as a consequence of an abnormal immune response in the presence of a single murine pathogen, H. hepaticus. The interaction of host immunity and a single pathogen in this murine system provides a novel model of human IBD, an immunity-mediated condition triggered by bacterial infection.